Redefining library learning Facilities in Malaysia : Lesson from Frank Lloyd Wright sustainable approach in spatial and landscape design - Nurakmal, Abdullah@ Goh Tuo Ho; Utaberta, Nangkula; Spalie, N.; Mazlan, Mohd Tahir (Elsevier Science, Ltd., 2011)
The main objective of this paper is to initiate and open a wider discussion on library design and learning facilities in Malaysia. It tries to take some lesson from one of the greatest modern American Architect which is Frank Lloyd Wright. The discussion itself will consist of four (4) parts. First part will discuss on the current problem and situation in reading and library issues in Malaysia while the second part will try to explore and review on the definition of outdoor learning with its importance and character in learning environment. The third part will focused on the Frank Lloyd Wright’s sustainable approaches in spatial and landscape arrangement while the last part will do some analysis and comparison which result on the suggestion and recommendation for outdoor learning facilities design in Malaysia. With some understanding from the established environmental approaches of Frank Lloyd Wright’s above it is expected that we can reconstruct and redefine some framework and guideline for future outdoor facilities design in Malaysia.